The relationship between diet and weight training with ideal body shape among members of Katamso Fitness Centre, Medan City - Sebayang, Robby Gunawan; Polem, Fahmi; Siregar, Hesti Despita; Putri, Lenni Dianna; Kunardi, Sidharta; Fransisca, Silvia; Bestari, Welas; Tarigan, Antje Irmella; Janice, Janice; Arhamni, Ade; Kurniawan, Evan (Buletin Kedokteran & Kesehatan Prima, 2025)
Katamso Fitness Centre is a gym surrounded by individuals aiming for an ideal and healthy physique. Members typically join to address less-than-ideal body weight and seek weight training to achieve their desired body shape—transforming from thin to muscular, or from overweight to lean, while also burning calories for overall health and fitness. This study employed a Chi-Square statistical test using SPSS for Windows, with a significance level of α=0.05. This analysis aimed to examine the relationship between independent and dependent variables. The research findings from 86 respondents indicate that the majority, 57 (66.3%), had a more ideal body shape. For diet patterns, the majority, 66 (76.7%), reported "sufficient." Regarding weight training, most respondents, 54 (62.8%), engaged in a "moderate" level.The relationship between diet patterns and ideal body shape among Katamso Fitness Centre members in Medan City showed a P-value of α>0.05, leading to the acceptance of Ha as significant. Conversely, the relationship between weight training and ideal body shape among members of the fitness center in Medan City showed a P-value of α<0.05, also leading to the acceptance of Ha as significant.